Geologi dan Identifikasi Cebakan Bijih di Daerah Batubesi, Belitung Timur - Ngadenin, Ngadenin; Indrastomo, Frederikus Dian; Karunianto, Adhika Junara; Rakhma, Ersina (EKSPLORIUM, 2017)
The Batubesi area in Belitung Timur is located in the eastern part of the Southeast Asian granites tin belt zone, so that it expected as a potential area for the occurence of ore deposit such as iron and cassiterite associate with monazite and other accessories minerals. The study aimed to understand the geological setting and to determine the occurrence of primary ore deposit and its radioactive accessories minerals. The methodologies in this research are geological mapping, uranium and thorium grade measurement, petrography, mineragraphy and grain counting analysis. The area composed by granite and metasandstone units. Types of granites are biotite and hornblende granites. The geological structures founded in this area are SW-NE sinistral and NW-SE dextral faults. Ore deposit in the area is primary iron ore deposits of skarn iron tin polymetallic type where magnetite is the main mineral while monazite and zircon are radioactive accessories minerals. The other accessories minerals are hematite, ilmenite, cassiterite, and rutile.